Red Blood Cell-Derived Iron Alters Macrophage Function in COPD - James M. Baker; Molly Hammond; Josiah Dungwa; Rajesh Shah; Angeles Montero-Fernandez; Andrew Higham; Simon Lea; Dave Singh (Biomedicines, 2021)
Lung macrophage iron levels are increased in COPD patients. Lung macrophage iron levels are thought to be increased by cigarette smoke, but the role of red blood cells (RBCs) as a source of iron has not been investigated. We investigate RBCs as a potential source of alveolar iron in COPD, and determine the effect of RBC-derived iron on macrophage function. We used lung tissue sections to assess RBC coverage of the alveolar space, iron and ferritin levels in 11 non-smokers (NS), 15 smokers (S) and 32 COPD patients. Lung macrophages were isolated from lung resections (n = 68) and treated with hemin or ferric ammonium citrate (50, 100 or 200 μM). Lung macrophage phenotype marker gene expression was measured by qPCR. The phagocytosis of Non-typeable Haemophilus influenzae (NTHi) was measured by flow cytometry. Cytokine production in response to NTHi in iron-treated macrophages was measured by ELISA. Lung macrophage iron levels were significantly correlated with RBC coverage of the alveolar space (r = 0.31, p = 0.02). Furthermore, RBC coverage and lung macrophage iron were significantly increased in COPD patients and correlated with airflow obstruction. Hemin treatment downregulated CD36, CD163, HLA-DR, CD38, TLR4, CD14 and MARCO gene expression. Hemin-treated macrophages also impaired production of pro-inflammatory cytokines in response to NTHi exposure, and decreased phagocytosis of NTHi (200 μM: 35% decrease; p = 0.03). RBCs are a plausible source of pulmonary iron overload in COPD. RBC-derived iron dysregulates macrophage phenotype and function.